another inductive proof

shakalandro

New member
Joined
Nov 29, 2008
Messages
36
Let u[sub:21min9po]n[/sub:21min9po] be the nth fibonacci number. Prove, by induction on n (without using the Binet formula) that

u[sub:21min9po]m+n[/sub:21min9po] = u[sub:21min9po]m-1[/sub:21min9po]u[sub:21min9po]n[/sub:21min9po] + u[sub:21min9po]m[/sub:21min9po]u[sub:21min9po]n+1[/sub:21min9po]

for all positive integers m and n.

Deduce, again using induction on n, that u[sub:21min9po]m[/sub:21min9po] divides u[sub:21min9po]mn[/sub:21min9po]
 
Start with n = 0 and verify (I'll leave that to you)

Now use the WEAK law of Induction:

Assume true for all k < n. [Not just for k = n-1]

u[m+k] = u[m-1]u[k] + u[m]u[k+1] for all k < n << the for all makes it the weak law.

Prove

u[m+n] = u[m-1]u[n] + u[m]u[n+1]

u[m+n] = u[m+n-1] + u[m+n-2]


u[m+n-1] = u[m-1]u[n-1] + u[m]u[n] << by assumption
u[m+n-2] = u[m-1]u[n-2] + u[m]u[n-1]<< by assumption
-------------------- ADD ------------------
u[m+n] = u[m-1]u[n-1] + u[m]u[n] + u[m-1]u[n-2] + u[m]u[n-1]

Factor, etc:

u[m+n] = u[m-1](u[n-1] + u[n-2]) + u[m](u[n] + u[n-1])

You can finish up.
 
daon said:
Start this inductive proof with n=1.

I think the custom is to write the Fibonacci sequence as starting with

F[0] = 0
F[1] = 1
and then
F[n] = F[n-1] + F[n-2]

That's why I wrote to start at n = 0. Naturally you could do it starting at n = 1, and having the sequence go:

F[1] = 1
F[2] = 1
and then
F[n] = F[n-1] + F[n-2]

But starting as I suggested makes the 'base case' so simple even a cave-man could do it. (Please don't send me any letters.)
 
You're right, but I was merely pointing out the problem states that m and n are positive.
 
Okay, I understand the first part completely now, but how would one prove that u[sub:1nixemjj]m[/sub:1nixemjj] | u[sub:1nixemjj]mn[/sub:1nixemjj]
 
Show the initial case.

Assume \(\displaystyle u_m | u_{mn}\).

WTS: \(\displaystyle u_{m} | u_{m(n+1)}\).

Use the first proposition:

[1] ... \(\displaystyle u_{m(n+1)} = u_{mn+m} = u_{mn-1}u_{m} + u_{mn}u_{m+1}\)

By our I.H., \(\displaystyle u_{mn} = k*u_{m}\)

Substituting into [1], we have:

[2] ... \(\displaystyle u_{m(n+1)} = u_{mn-1}u_{m} + k*u_mu_{m+1} = u_m(u_{mn-1}+k*u_{m+1})\)

Got it?
 
shakalandro said:
Let u[sub:2l4kabps]n[/sub:2l4kabps] be the nth fibonacci number. Prove, by induction on n (without using the Binet formula) that

u[sub:2l4kabps]m+n[/sub:2l4kabps] = u[sub:2l4kabps]m-1[/sub:2l4kabps]u[sub:2l4kabps]n[/sub:2l4kabps] + u[sub:2l4kabps]m[/sub:2l4kabps]u[sub:2l4kabps]n+1[/sub:2l4kabps]

for all positive integers m and n.

Deduce, again using induction on n, that u[sub:2l4kabps]m[/sub:2l4kabps] divides u[sub:2l4kabps]mn[/sub:2l4kabps]

Yes, that makes perfect sense, thankyou, it seems so easy afterwards

And you did not have to do anything to have it solved!
 
Top